The Abuse of Practices Ta'ruf in the View of Islamic Law - Al Azmy, M. Abdurrahman (Prodi Hukum Ekonomi Syariah (Muamalah), 2024)
Ta'aruf is a method of introduction between men and women with the aim of marriage, which is carried out through the intermediary of ustadz or parents. However, the practice of ta'aruf is currently experiencing a shift in meaning due to the times, including its implementation online. This study aims to analyze the forms of deviation in the practice of ta'aruf based on the perspective of Islamic law. Using a descriptive qualitative approach, this study identifies deviations that often occur, such as fraud, sexual harassment, and behavior approaching adultery. Data were obtained through in-depth interviews and literature review. The results show that deviations in ta'aruf are often due to a lack of understanding of the principles of sharia, the influence of technology, as well as weak family supervision and mediators. The research also emphasizes the important role of the family and Islamic institutions in ensuring that the practice of ta'aruf is in accordance with Islamic teachings. Research recommendations include strengthening education on the concept of ta'aruf, stricter supervision of online practices, and the development of comprehensive shar'i guidelines to prevent abuse in this process